Policy brief: adaptive cycling equipment for individuals with neurodevelopmental disabilities as durable medical equipment - Gannotti, Mary E.; O’Neil, Margaret E.; Fragala-Pinkham, Maria; Gorton, George E.; Whitney, Daniel G. (Frontiers in Rehabilitation Sciences, 2023)
- Durable medical equipment policies require that the equipment be medically necessary, and adaptive cycles (bicycles or tricycles) are usually not deemed medically necessary - Individuals with neurodevelopmental disabilities (NDD) are at high risk for secondary conditions, both physical and mental, that can be mitigated by increasing physical activity. - Significant financial costs are associated with the management of secondary conditions - Adaptive cycling can provide improve physical health of individuals with NDD potentially reducing costs of comorbidities. - Expanding DME policies to include adaptive cycling equipment for qualifying individuals with NDD can increase access to equipment - Regulations to insure eligibility, proper fitting, prescription, and training can optimize physical - Programs for recycling or repurposing of equipment are warranted to optimize resources.